2021
DOI: 10.5070/t34151426
|View full text |Cite
|
Sign up to set email alerts
|

Teaching in 2020: Preliminary Assessments

Abstract: By the end of summer 2020, the COVID-19 pandemic had upended higher education by requiring immediate adaptation by students, teachers, and institutions to new sets of limitations. What did this period of crisis mean for current and future teaching and learning? A rapid qualitative assessment presented here seeks to begin a sustained conversation around instructors' experiences. The anthropology professors interviewed in this study found that preexisting conditions in higher education resulted in pedagogical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Anthropological fieldwork possibilities, for students and faculty alike, have been significantly affected by the pandemic, with implications for access to experiential, hands-on learning options (Santos 2021). Nevertheless, Cheuk (2021) has noted that online ethnographic projects, spurred by the necessity of pandemic teaching and learning changes, can deepen public engagement and offer new possibilities.…”
Section: Insights and Outcomes: What Did We Learn About Developing An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropological fieldwork possibilities, for students and faculty alike, have been significantly affected by the pandemic, with implications for access to experiential, hands-on learning options (Santos 2021). Nevertheless, Cheuk (2021) has noted that online ethnographic projects, spurred by the necessity of pandemic teaching and learning changes, can deepen public engagement and offer new possibilities.…”
Section: Insights and Outcomes: What Did We Learn About Developing An...mentioning
confidence: 99%
“…Second, there have been various discussions about the teaching implications, challenges, and opportunities of COVID-19, both within and beyond anthropology (e.g., Cheuk 2021;Christian, McCarty, and Brown 2021;Daurio and Turin 2021;Jacobs et al 2021;Jenks 2021;Kim et al 2021;Mandache et al 2021;Russell et al 2021;Santos 2021) as well as about the stresses, challenges, and uncertainties that students have, and continue to experience, in the context of the pandemic (e.g., Lee, Jeong, and Kim 2021;Moore, Petrie, and Slavin 2022;Salvador et al 2021;Villani et al 2021). We were aware that the combination of uncertainties about the pandemic, changes in teaching formats and approaches, and pre-existing vulnerabilities (Santos 2021;Kelly 2022) had affected, and continued to affect, our students. As Russell et al (2021) have noted, the pandemic demands attention in anthropology classes.…”
mentioning
confidence: 99%
“…This gender inequity may be related to truncated careers or intermittent work due to women's predominant role as mothers. In education, for example, it was found that during the pandemic, male researchers submitted more publications on average than female researchers because women had a greater burden of hours devoted to home and childcare than their male colleagues (Santos, 2021). This could have allowed the male researchers to maintain their productivity, and therefore, any bonuses or financial incentives that they could receive.…”
Section: Financementioning
confidence: 99%
“…During the pandemic, many teachers at retirement age had to cope with difficult equipment conditions, poor connectivity, and lack of training -as some have never taught online before (Santos, 2021). Thus, an increase in digital literacy among older workers took place during the pandemic (Carr et al, 2021).…”
Section: Psychological Well-beingmentioning
confidence: 99%